Diversity oriented one-pot three-component sequential synthesis of annulated benzothiazoloquinazolines - Kumar, Mahendra (Springer, 2012)
Annulated benzothiazoloquinazolines have been synthesized by a diversity oriented simple and convenient synthesis involving one-pot three-component reaction of substituted 2-aminobenzothiazoles with α-tetralone and aromatic/heteroaromatic aldehydes in ethanol in the presence of catalytic amount of triethylamine. The synthesized compounds have been characterized by their elemental analyses and spectral data.